GC-MS ANALYSIS OF ETHYL ACETATE FRACTIONS OF QUST AL HINDI (Saussurea lappa) ROOT - Sukmawati; A. Muflihunna (Universal Journal of Pharmaceutical Research, 2025)
Background: Qutsh al Hindi (Saussurea lappa), commonly known as Indian wood, is a traditional medicine that had been used empirically as anti-inflammatory and pneumonia. Its potential as anti-inflammatory activity is proven by many researches in vitro and in vivo. Aim and objective: This study aims to identifying active compounds from the ethyl acetate fraction of Qutsh al Hindi (S. lappa) using GC-MS. Method: The extract was obtained by powder of S. lappa roots using maceration method and evaporated to obtained thick extract. Then, the isolate of extract would be fractionated using n-hexane and ethyl acetate. The compounds that carried out by fractionation would be identified using GC-MS. Result: Based on this research, the analysis of S. lappa ethyl acetate fraction showed 119 compounds using GC-MS. Other supporting factors using Mass Chromatography. The result was one of target compound identified, i.e. β-cyclocostunolide, a derivate compound from costunolide that has an anti-inflammatory activity. Conclusion: It can be concluded that a fraction of S. lappa roots ethyl acetate contain β-cyclocostunolide as anti-inflammatory compounds. Peer Review History: Received 11 September 2024; Reviewed 12 November; Accepted 25 December; Available online 15 January 2025 Academic Editor: Dr. Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewers: Dr. Rola Jadallah, Arab American University, Palestine, rola@aauj.edu Dr. Sabah Hussien El-Ghaiesh, Tanta University, Egypt, s.ghaiesh@gmail.com